2019
DOI: 10.3390/w11030419
|View full text |Cite
|
Sign up to set email alerts
|

Reservoir Operation Policy based on Joint Hedging Rules

Abstract: When the water supply capacity of the reservoir is small, hedge rule (HR) can be applied to reduce the risk of unacceptably large damage from water shortage during drought. Moreover, in water-receiving areas of water diversion project, it is important to reduce transfer based on HR when the water-receiving area is in a wet period so as to reduce the water transfer cost. This paper improved the traditional HR and proposed a new kind of hedging rule named joint hedging rule (JHR). JHR was applied to Yuqiao Reser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…ese mean that optimal rule curves from using HR attempt to retain water by limiting the water discharge during dry season according to the concept of using HR [15,18]. It also indicates that the upper rule curves from using HR criteria are higher than upper rule curves when using SOP criteria in the end of rainy season (Oct.-Nov.).…”
Section: E E Ciency Of Mpa Rule Curves Considering Hr and Sopmentioning
confidence: 96%
See 2 more Smart Citations
“…ese mean that optimal rule curves from using HR attempt to retain water by limiting the water discharge during dry season according to the concept of using HR [15,18]. It also indicates that the upper rule curves from using HR criteria are higher than upper rule curves when using SOP criteria in the end of rainy season (Oct.-Nov.).…”
Section: E E Ciency Of Mpa Rule Curves Considering Hr and Sopmentioning
confidence: 96%
“…It is concluded that the situations of water shortage and excess water when using the obtained rule curves from MPA considering HR were fewer than situations of water shortage and excess water of using the obtained rule curves from MPA considering SOP. erefore, the HR criteria control water release limitedly for saving water in order to alleviate water de cit in the next dry season [15,18]. However, the SOP criteria control release of water in order to meet target demand for all considered duration times according to many previous studies [11,30,32,33].…”
Section: E E Ciency Of Mpa Rule Curves Considering Hr and Sopmentioning
confidence: 99%
See 1 more Smart Citation
“…4 in case of K P equal to 1) can be divided into three main areas: (1) the reservoir is depleted, or in some cases emptied, if insufficient available water cannot guarantee that target water demand is met; (2) the reservoir is filled during conditions in which water availability is higher than target demand; and (3) water is spilled downstream when reservoir volume and target water demand exceed reservoir capacity. However, during drought periods, it may not be possible to reach the volume target because of the inability of standard operational policy of rationing water release for future demand when water is insufficient (Wang et al 2018, Men et al 2019. For this reason, hedging rules can be used to create a trade-off between ongoing demands and adequate reservoir volume, minimizing the impact of drought conditions (Shiau 2009, Baes andBürgisser 2013).…”
Section: Reservoir Systemmentioning
confidence: 99%
“…While during dry periods, when the reservoir storage level falls, the reservoir release is reduced to maintain a sufficient amount of water remaining in the reservoir for future water supply. This kind of situation seeks appropriate multi-criteria decision-making methods to optimally solve the existing conflicting trade-offs objectives, meeting ongoing water users demand, minimizing flood risks, and ensuring adequate reservoir storage when inflow is insufficient [136]. The MCDM methods are useful in situations where there is a decision-making that must meet multiple objectives in an integrated manner [135].…”
Section: Water Shortage and Flood Problemsmentioning
confidence: 99%